2018
DOI: 10.2174/1874312901812010050
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Osteopenia and Osteoporosis Among Malaysian Type 2 Diabetic Patients Using Quantitative Ultrasound Densitometer

Abstract: Background:Type 2 Diabetes Mellitus (T2DM) and osteoporosis are both chronic conditions and the relationship between them is complex.Objective:The aims of this study were to assess the prevalence of Low Bone Mineral density (LBMD, i.e., osteopenia and osteoporosis), as well as, the difference and associations between Quantitative Ultrasound Scan (QUS) parameters with socio-demographic data and clinical related data among T2DM in Penang, Malaysia.Method:An observational, cross-sectional study with a convenient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 100 publications
0
11
1
Order By: Relevance
“…The osteoporotic conditions results of the sample population were previously reported 12. In brief, the average T-score value for the patients was (-1.67; SD 0.83) with (median: -1.65), (range: -3.4 to 1.2) and (CI 95%: -1.75 to -1.59)).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The osteoporotic conditions results of the sample population were previously reported 12. In brief, the average T-score value for the patients was (-1.67; SD 0.83) with (median: -1.65), (range: -3.4 to 1.2) and (CI 95%: -1.75 to -1.59)).…”
Section: Resultsmentioning
confidence: 75%
“…Nevertheless, indirect relations may explain the results. Other studies among T2DM patients showed that poor glycaemic control, long duration of diabetes and treatment type seem to play a key role in decreasing or increase bone mass 10,12. There was only a significant association and difference in OKT-M score with diastolic blood pressure groups (DBP).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, point biserial correlation and Ferguson's sigma values which are an item-total correlation and discriminatory power, respectively, were within the acceptable range and indicated that the tool is reliable and discriminating [23,32]. *Sum of the potential range for the Exercise subscale and Calcium intake subscale was larger than total potential range because the two subscales shared nine common questions (1)(2)(3)(4)(5)(6)(7)(8)(9). The results showed low correct answer frequencies for all dimension with low overall knowledge score.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of osteoporosis associated to diabetes mellitus is less acknowledged, and, to date, no clear conclusions have been reached due to the contradiction among researchers; they have reported Low, Moderate and High bone mass in diabetic post-menopausal women 9 . To the ulterior knowledge of researcher, this was the first extensive field study using calcaneal QUS to determine and identify the prevalence of Osteopenia and Osteoporosis, in diabetic postmenopausal women 10 .…”
Section: Resultsmentioning
confidence: 99%